Discrimination and characterization analysis of key flavor compounds from Tianshui Zanthoxylum bungeanum shells and seeds by GC×GC-TOFMS and chemometrics - Liping Lu; Mengyu Wang; Runjie Cui; Yanli Zhu; Shanshan Liu; Ziyi Yin; Dandan Gao (Food Chemistry: X, 2025)
Flavor compounds influence consumer acceptance of Zanthoxylum bungeanum Maxim (Chinese pepper) berries, so detailed knowledge of its sensory characteristics and flavor compound composition are vital for assessing sensory quality and conserving genetic resources. This study identified and characterized the key flavor compounds in Z. bungeanum shells (SH) and seeds (SD) from the seven growing regions of Tianshui city, Gansu province, using GC × GC-TOFMS and chemometrics. The flavor compounds identified in Z. bungeanum were in the compound classes of hydrocarbons, heterocyclic compounds, ketones, alcohols, esters, aldehydes and carboxylic acids. Multivariate statistical analysis distinctly differentiated between SH or SD samples from the seven regions. The key differential flavor compounds in SH were isophorone, limonene, 2-butanone and 5-methyl-2-hexanone, and in SD were acetylacetone, camphor, 2-propanamine, 2-butenal, formic acid and 1,2,4-trimethyl-benzene. These findings provide a foundation to promote large-scale cultivation of specific local Z. bungeanum species.